Analysis of a gene family for PDF-like peptides from Arabidopsis - Reza Omidvar (Nature Portfolio, 2021)
Abstract Plant defensins are small, basic peptides that have a characteristic three-dimensional folding pattern which is stabilized by four disulfide bridges. We show here that Arabidopsis contains in addition to the proper plant defensins a group of 9 plant defensin-like (PdfL) genes. They are all expressed at low levels while GUS fusions of the promoters showed expression in most tissues with only minor differences. We produced two of the encoded peptides in E. coli and tested the antimicrobial activity in vitro. Both were highly active against fungi but had lower activity against bacteria. At higher concentrations hyperbranching and swollen tips, which are indicative of antimicrobial activity, were induced in Fusarium graminearum by both peptides. Overexpression lines for most PdfL genes were produced using the 35S CaMV promoter to study their possible in planta function. With the exception of PdfL4.1 these lines had enhanced resistance against F. oxysporum. All PDFL peptides were also transiently expressed in Nicotiana benthamiana leaves with agroinfiltration using the pPZP3425 vector. In case of PDFL1.4 this resulted in complete death of the infiltrated tissues after 7 days. All other PDFLs resulted only in various degrees of small necrotic lesions. In conclusion, our results show that at least some of the PdfL genes could function in plant resistance.